1976
DOI: 10.1111/j.1399-6576.1976.tb05008.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Analgesia —II: Prolongation in the Early Postoperative Period by Continuous Injection of 1.0% Bupivacaine

Abstract: Sixteen patients were given thoracic epidural analgesia at the T5-T6 level with 2 ml of 1.0% bupivacaine solution plain for pain relief after upper abdominal surgery. In 13 cases the analgesia was prolonged by continuous injection of 1.0% bupivacaine for 24 or 48 h. Onset time and segmental spread of the analgesia are presented as well as segmental spread, intensity of the blockade, and peak expiratory flow rates during prolongation. Signs of tachyphylaxis were noticed, and also signs of accumulation of bupiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
2

Year Published

1976
1976
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
3
14
2
Order By: Relevance
“…Bromage [6] found that it is the total local anesthetic dose, and not the total volume, which determines the spread and quality of analgesia. Others have confirmed this finding, after both lumbar [7] and midthoracic [8] epidural administration. Nevertheless, it remains unclear in the literature whether the concentration influences the quality of pain relief during epidural analgesia when the total dose is held constant [9][10][11].…”
Section: Introductionsupporting
confidence: 65%
“…Bromage [6] found that it is the total local anesthetic dose, and not the total volume, which determines the spread and quality of analgesia. Others have confirmed this finding, after both lumbar [7] and midthoracic [8] epidural administration. Nevertheless, it remains unclear in the literature whether the concentration influences the quality of pain relief during epidural analgesia when the total dose is held constant [9][10][11].…”
Section: Introductionsupporting
confidence: 65%
“…Long term epidural infusions ofbupivacaine for prevention or relief of postoperative pain have been shown to result in prolonged and more extensive accumulation (Renck et al 1976;Ross et aI. 1980).…”
Section: Concentrations During Continuous Epidural Anaesthesia 297mentioning
confidence: 97%
“…It thus seems that the volume is not important when mixtures of bupivacaine and fentanyl in the studied concentrations are infused epidurally at a low thoracic level. For epidural bupivacaine alone, dose has been shown to be more important than volume (12)(13)(14). It has also been reported that the infusion of a more diluted bupivacaine solution gives better analgesia than a more concentrated solution (11,15).…”
Section: Discussionmentioning
confidence: 99%